Chemoprophylaxis for the prevention of endophthalmitis after cataract surgery: patterns of use and economic costs - Rosha, Deepinder Singh (Curtin University, 2006)
Objectives: The objectives of study were to (i) examine the regional differences in methods of performing cataract surgery across different jurisdictions in Australia and New Zealand (ii) identify risk factors for post-operative endophthalmitis and (iii) explore the implication of changes in surgical practice on the number of cases of post-operative endophthalmitis and resultant net cost to health system. Methods: Cataract surgeons across Australia and New Zealand were surveyed about their demographics, surgical techniques, use of pre- and post-operative antibiotics and antiseptics and cases of post-operative endophthalmitis. Statistical analysis was conducted to determine the regional variations in the use of methods of chemoprophylaxis and surgical practices. Multivariate Poisson regression was performed to identify factors associated with the incidence of post-operative endophthalmitis. A cost analysis was conducted to determine the impact of an increased use of chemoprophylatic treatment on the number of cases of post-operative endophthalmitis and net cost savings to the health system from its use. In addition, the results of the current survey of surgical practices of cataract surgeons was compared with those from an earlier survey conducted approximately 10 years ago. Result: The response to the survey of ophthalmologists was 82%, but after excluding ophthalmologists who did little or no cataract surgery, the study sample comprised 540 participants of the 896 who were initially sent the survey. Participating cataract surgeons reported 162,120 cataract surgeries and 92 cases of post-operative endophthalmitis, an incidence rate of 0.056%. Regional variations were found in the methods of chemoprophylaxis and surgical techniques.Chloramphenicol was the most frequently used topical antibiotic in Australia, while neomycin was used by majority of cataract surgeons in New Zealand. The only notable change found over the past decade was a sharp fall in use of subconjunctival antibiotics from 75% to 45% in the current survey. A slight increase in use of post-operative topical antibiotics was noticed. Subconjunctival injection of antibiotics was the only form of chemoprophylaxis associated with a reduction in incidence of endophthalmitis. Results from this survey indicated that cataract surgeons routinely using corneal or limbal incisions had an incidence of endophthalmitis considerably higher than those surgeons routinely using scleral wounds, whilst surgeons routinely using temporally sited wounds had almost half the incidence of endophthalmitis compared to surgeons using superior wounds. The cost implications of subconjunctival gentamycin injection for chemoprophylaxis were examined. Additional costs of subconjunctival antibiotics were subtracted from the reduced cost of treating fewer cases endophthalmitis. There would potentially be a net saving to the Australian health system of $ 110,354 if all cataract surgeons used subconjunctival chemoprophylaxis. Conclusion: Regional variation in chemoprophylaxis and surgical techniques did not entirely explain differences in post-operative endophthalmitis incidence. Subconjunctival antibiotics would only need to reduce the incidence of endophthalmitis by 15% for it to be cost-effective.